PENERAPAN METODE PEMBIASAAN DALAM MENINGKATKAN HAFALAN DOA SEHARI-HARI PADA ANAK USIA 5-6 TAHUN DI KELOMPOK BERMAIN KASIH IBU KECAMATAN SEMPARUK TAHUN PELAJARAN 2022-2023 - Nurbaiti, Nurbaiti (Lunggi Journal, 2024)
Planning habituation methods in improving the memorization of daily prayers for clildren aged 5-6 years in the mothers love play group in the half district half og the 2022-2023 academic year,faculuty of tarbiyah muhammad syafiuddin sambas islamic regious institute 2023. Planning habituation methods to improve daily prayer memorization for children aged 5-6 years the ai m of this research is to revel about 1.) planning habituation methods to improve the memorization of daily prayesr for clildren aged 5-6 years in sub-district mothers love play groups for the 2022-2023 academic year 2.) implemenentation of the habituation method in playning games with subdistrict motheres for half of the 2022-2023 academic year 3.) clidren aged 5-6 years in the half-year sub-district mothers love play group in the half-year sub-districts mothers love play group for the 2022-2023 school year.the research uses qualitative phenomenological research data collection.the analysis technique used is data reduction the research results show that : 1.) Planning habituation methods to improve the memorization of daily prayers in sub-district mothers love play groups for the 2022-2023 academic year 2.) implementation of the habituation method in improving the memorization of daily prayes in for children aged 5-6 years in the sub-district mothers love play group for the 2022-2023 school year consists of several steps,namely introduction,main and closing 3.) evaluate the habituation method in improving the daily prayer memorization of children aged 5-6 years 2022-2023 by collecting star sticker and then ajusting it to the cognitive aspect of children memorizing daily prayrs that they daily prayes that they want to achieve.